The Effects of Training Program for Enhancing Meaning in Life of University Students - Chaiwongwilan, Paween; Longthong, Nathawat (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The research was quasi-experiment and aims to study the result of the training program for enhancing meaning in life of university students. The participants were 30 volunteer university students in the academic year 2020 at Chiang Mai University, divided into 2 groups which are experimental groups and control groups with 15 participating in each group. The experiment group was participated in the training program for enhancing meaning in life in 15 times in each session. However, the control group wasn’t participated in this program. The statistics use to analyzed are t-test for a dependent sample and independent sample data meaning in life score. As a result, 1. After participated the program The experiment groups have a higher level of meaning in life than before participating in the training program for enhancing meaning in life of university students with statistical significant .01 levels. 2. The experimental group posttest score was found significantly higher than the control group posttest score. with statistical significant .01 levels.